Deep North Atlantic Last Glacial Maximum Salinity Reconstruction. Issue 7 (12th July 2021) - Homola, Kira; Spivack, Arthur J.; Murray, Richard W.; Pockalny, Robert; D'Hondt, Steven; Robinson, Rebecca
Abstract: We reconstruct deep water‐mass salinities and spatial distributions in the western North Atlantic during the Last Glacial Maximum (LGM, 19–26 ka), a period when atmospheric CO2 was significantly lower than it is today. A reversal in the LGM Atlantic meridional bottom water salinity gradient has been hypothesized for several LGM water‐mass reconstructions. Such a reversal has the potential to influence climate, ocean circulation, and atmospheric CO2 by increasing the thermal energy and carbon storage capacity of the deep ocean. To test this hypothesis, we reconstructed LGM bottom water salinity based on sedimentary porewater chloride profiles in a north‐south transect of piston cores collected from the deep western North Atlantic. LGM bottom water salinity in the deep western North Atlantic determined by the density‐based method is 3.41–3.99 ± 0.15% higher than modern values at these sites. This increase is consistent with: (a) the 3.6% global average salinity change expected from eustatic sea level rise, (b) a northward expansion of southern sourced deep water, (c) shoaling of northern sourced deep water, and (d) a reversal of the Atlantic's north‐south deep water salinity gradient during the LGM. Plain Language Summary: Twenty thousand years ago, the atmosphere had a much lower temperature and contained less insulating carbon dioxide (CO2 ) gas than it did even before the human induced CO2 rise of the last centuries. Confirming if the carbon "missing" from the atmosphere 20, 000 years ago was stored away in the deep ocean will help us predict where the carbon humans add to the atmosphere will end up over the next few millennia. We find the temperature and amount of salt (salinity) in today's waters by measuring them directly, but to find them in the past ocean we measure chemical compounds that are buried over time in the seafloor. In this study, we measure the density of water collected from the north Atlantic seafloor to estimate the past salinity. Our results support previous findings that 20, 000 years ago the deep Atlantic was filled with more carbon‐rich water that sank from the surface in the Southern Ocean than in today's Atlantic, accounting for up to two‐thirds of the carbon "missing" from the atmosphere 20, 000 years ago. Key Points: Paleosalinities of Last Glacial Maximum (19–26 ka) North Atlantic Bottom waters are 3.41–3.99 ± 0.15% higher than modern values New paleosalinities support expansion of salty, southern sourced water displacing fresher, northern sourced water in the Last Glacial Maximum (LGM) deep Atlantic Paleosalinities are more precise when from porewater densities measured on ship from cores that span the LGM porewater chloride maximum